Porcine somatotropin and dietary lysine influence bone mineralization and mechanical properties in finishing swine - B R Schricker; Robert D Goodband; Robert H Hines; Jim L Nelssen; Donald H Kropf; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1989)
The femur, a rib, and third phalanx of the second digit from the front foot were collected from 108 barrows (initial wt = 125 lb) and analyzed to determine the effects of porcine somatotropin (pST) and dietary lysine on bone mineralization and mechanical properties. In Exp. 1, pigs were injected daily with 4 mg pST and fed diets containing .6, .8, 1.0, 1.2, or 1.4% lysine; 1.0% Ca; and .8% P. Control pigs (placebo injection) received the .6% lysine diet. Bone wall thickness (BWT) of the femur increased but ash content decreased as dietary lysine level increased. Stress values and ash content of the rib also decreased with increasing dietary lysine level. In Exp. 2, pigs were injected with either 4 or 8 mg/d pST and fed diets containing .8, 1.0, 1.2, or 1.4% lysine; 1.1% Ca; and 1.0% P. Control pigs received the .8% lysine diet. Increasing pST dosage increased BWT of the femur, but decreased ash content. In the rib, increasing pST dosage reduced stress values, modulus of elasticity, and ash content. Increasing lysine level resulted in increased BWT of the femur and decreased ash content of rib, femur and phalanx. These data indicate that pST administration in conjunction with increasing lysine levels decreases bone mineralization but increases BWT of finishing pigs.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Porcine somatotropin; Lysine; Finishing pigs; Bone mechanical properties